Prevalence of problematic Internet use and its association with quality of life among undergraduate nursing students in the later stage of COVID‐19 pandemic era in China. Issue 6 (16th September 2021) - Cai, Hong; Xi, Hai‐Tao; Zhu, Qianqian; Wang, Zhiwen; Han, Lin; Liu, Shuo; Bai, Wei; Zhao, Yan‐Jie; Chen, Li; Ge, Zong‐Mei; Ji, Mengmeng; Zhang, Hongyan; et al.
Abstract: Background and Objectives: The prevalence of problematic Internet use (PIU) in the post‐COVID‐19 pandemic era is not known. This cross‐sectional study aimed to determine the prevalence of PIU among baccalaureate nursing students (hereafter: nursing students) in the post‐COVID‐19 era. Methods: A total of 1070 nursing students were consecutively invited to participate in this study from the nursing schools of five universities. PIU and quality of life (QOL) were assessed using the Internet Addiction Test (IAT) and the World Health Organization Quality of Life Scale Brief Version (WHOQOL‐BREF), respectively. t Tests, χ 2, tests, and Kruskal–Wallis tests were used to compare basic demographic and clinical characteristics between participants with and without PIU. Binary logistic regression analysis was used to examine independent correlates. Results: The prevalence of PIU was 23.3% (95% confidence interval [CI]: 20.7%–25.8%). Multiple logistic regression analysis revealed that second‐ ( p  = .024) and third‐year ( p  = .012) students were more likely to suffer from PIU compared with first year students. Students with more severe depressive ( p  = .014) and anxiety symptoms ( p  = .011) were independently and significantly associated with more severe PIU. After controlling for covariates, nursing students with PIU had a lower overall QOL score ( p  = .002). Conclusion and Scientific Significance: Problematic Internet use (PIU) was common among nursing students in the post‐COVID‐19 era. Considering the negative impact of PIU on QOL and academic performance, regular screening should be conducted and effective interventions implemented for nursing students with PIU. This was the first study on the prevalence of PIU among nursing students in the post‐COVID‐19 era. The findings of this study could help health professionals and education authorities to understand the patterns of PIU and its influence on QOL among nursing students and to allocate health resources and develop effective measures to reduce the risk of PIU in this population.